Platão e a formação cívica: educação para as democracias constitucionais atuais - Anézio, Letícia Regina (2025)
This dissertation proposes an analysis of Plato’s educational philosophy from the perspective of its potential liberating nature, with the aim of investigating its relevance to civic education in contemporary constitutional democracies. The study is based on a critical reading of The Republic and other Platonic dialogues, considering the role of education both as an instrument for ordering the polis and as a path for the moral and intellectual ascent of the soul. The research examines interpretations by scholars who emphasize the hierarchical and functionalist character of the Platonic model, in contrast with more emancipatory readings that highlight the formative and philosophical dimension of education. In the end, it is concluded that Plato’s educational proposal, although containing elements of social control, is nonetheless a liberating project, as it is capable of awakening in the individual a sense of restlessness and a desire to seek the truth – an awakening that offers meaningful foundations for building an active, ethical, reflective citizenship committed to the common good in today’s democratic societies. Based on these elements, the research adopts an exploratory character with a qualitative methodological approach